Smart grid application guide : Integrating Facilities with the Electric Grid. (ASHRAE, 2020)
This book provides building owners, managers, and designers with guidance on the smart grid, applicable smart grid standards and regulations, and design and operation of systems in this emerging industry. Smart Grid Applications Guide details the concrete steps needed to prepare a building-whether new construction or renovation-for integration with the smart grid. This guide includes sections on: Navigating regulatory environments that affect deployment of the smart grid; Demand-side management; Behind-the-meter distributed energy resources; Multiple-facility operation, including microgrids and customer aggregation for demand response; Meeting building needs during interruptions to grid services.